Factors Important Tourists to Visit Aranyik Historical Area in Nakorn Chum District, Thailand - Chantharaksa, Wanachaporn; Madhyamapurush, Warach (Journal of Cultural Approach, 2015)
This research aimed to find factors that important tourists to visit the Aranyik historical area, Nakhon Chum District, which is currently located in Mueang Kamphaeng Phet District, Kamphaeng Phet. Two objectives of this research were 1) to determine main factors that influence tourists to visit Aranyik historical area, Nakhon Chum District, and 2) to identify targeted tourists who will visit Aranyik historical area, Nakhon Chum District. This research focused on ten historical sites and temples in Aranyik historical area, Nakhon Chum District. A survey was designed using closed questions. The questions included in the survey were used to collect demographic and tourist information, the behaviors of tourists who visit historical sites, and factors that influences tourists to visit historical sites. The populations included in this research were tourists who visits those 10 historical sites (ancient temples and ancient ruined structures). Of the total population, three hundred and eighty-four tourists were asked to complete the survey by using the accidental sampling method. This research collected data from January to March 2014. Descriptivestatics including percentages, averages, and standard deviations were used to analyze data. The results indicated three most important factors that influenced tourists to visit historical sites in Aranyik historical area where the condition of historical structures, facilities at historical sites, and transportations to historical sites. Overall, the condition of historical structures was rated as important level. The condition of historical structures consisted of nine aspects (one the most important aspect, five important aspects; two fairly important aspects; and a slightly important aspect). For facilities at historical sites, an average score was 3.68. Facilities at historical sites had eleven aspects (four the most important aspects; three important aspects, two fairly important aspects, and two slightly important aspects). Transportations to historical sites were rated as important level. Transportations to historical sites contained seven aspects (two the most important aspects; four important aspects, and fairly important aspects).